2021
DOI: 10.4102/phcfm.v13i1.2724
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, attitudes and understanding of health professionals of interprofessional practice at a selected community health centre

Abstract: Background Despite being identified as a solution to the challenges related to healthcare service delivery, the incorporation of interprofessional practice (IPP) into clinical practice has been limited. To implement an interprofessional model of healthcare, successfully, health professionals need to have an understanding of IPP and its related content. Aim The aim of this study was to explore and describe the health professionals’ perceptions, attitudes and understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…All the studies were conducted in South Africa, as per the inclusion criteria ( Table 3 ). The articles covered two public hospitals (Nyoni, Grobler & Botma 2021 ; Waggie & Arends 2020 ), a community healthcare centre (Kock et al 2021 ), a semi-rural hospital (Maddocks et al 2018 ) and intensive care units (ICUs) in the public and private sectors (Ntinga & Van Aswegen 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies were conducted in South Africa, as per the inclusion criteria ( Table 3 ). The articles covered two public hospitals (Nyoni, Grobler & Botma 2021 ; Waggie & Arends 2020 ), a community healthcare centre (Kock et al 2021 ), a semi-rural hospital (Maddocks et al 2018 ) and intensive care units (ICUs) in the public and private sectors (Ntinga & Van Aswegen 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of IPCP into clinical practice is limited, both locally and internationally (Bierwas et al 2017 ; Kock, Mlezana & Frantz 2021 ). As a result, the impact of IPE on IPCP and clinical service delivery is not evident where the overall health of the population is concerned.…”
Section: Introductionmentioning
confidence: 99%
“… 22 Kock et al assessed the impact of implementing interprofessional practice (IPP) on the perceptions, attitudes, and understanding of health care professionals. 6 IPP was being implemented as a way to address interdisciplinary relationship challenges in health care practice. The findings of the study suggested that health care professionals lacked the understanding of and the ability to practically apply IPP.…”
Section: Conflict Resolutionmentioning
confidence: 99%
“…The study also showed that health care professionals expressed the necessity for interprofessional relationships, an environment that fosters IPP, and an environment that fosters a level of communication for changing the current health care work practice. 6 …”
Section: Conflict Resolutionmentioning
confidence: 99%
See 1 more Smart Citation